A systematic review reveals conflicting evidence for the prevalence of antibodies against the sialic acid ‘xenoautoantigen’ Neu5Gc in humans and the need for a standardised approach to quantification - Hutton, Esme; Scott, Emma; Robson, Craig N.; Signoret, Nathalie; Fascione, Martin A. (Frontiers in Molecular Biosciences, 2024)
Despite an array of hypothesised implications for health, disease, and therapeutic development, antibodies against the non-human sialic acid N-glycolylneuraminic acid (Neu5Gc) remain a subject of much debate. This systematic review of 114 publications aimed to generate a comprehensive overview of published studies in this field, addressing both the reported prevalence of anti-Neu5Gc antibodies in the human population and whether experimental variation accounts for the conflicting reports about the extent of this response. Absolute titres of anti-Neu5Gc antibodies, the reported prevalence of these antibodies, and the individual variation observed within experiments were analysed and grouped according to biological context (‘inflammation’, ‘xenotransplantation’, ‘biotherapeutic use’, ‘cancer’, and ‘healthy populations’), detection method, target epitope selection, and choice of blocking agent. These analyses revealed that the experimental method had a notable impact on both the reported prevalence and absolute titres of anti-Neu5Gc antibodies in the general population, thereby limiting the ability to ascribe reported trends to genuine biological differences or the consequence of experimental design. Overall, this review highlights important knowledge gaps in the study of antibodies against this important xenoautoantigen and the need to establish a standardised method for their quantification if the extent of the importance of Neu5Gc in human health is to be fully understood.